SOCIOCULTURAL THEORY OF LEARNING TO PROMOTE COMMUNICATIVE LANGUAGE TEACHING (EDUCATION IN THE 21ST CENTURY, 2025)
In recent years, language learning has been viewed from a very different angle concentrating on meaningful and purposeful interactions, collaborations between speakers. This has accordingly brought a shift from more traditional grammar-based language teachings based on repetitions and drills to communicative language teachings (CLT) based on pair work activities, role plays, group activities and project works. Thus, in the classroom teachers aim to design the curriculum in such a way that they can explore the opportunities of developing communicative competences. The urgency of communicative language teaching is reviewed in a number of corresponding studies such as the Common European Framework of References for Languages (CEFR), The Future of Education and Skills 2030 project by OECD and the Cambridge Life Competencies Framework. While this undoubtedly asserts the necessity of language teaching for communication we also need to understand how it aligns with the cognitive framework of the student in case of formal education. What theory can not only prove the necessity of communication but also pave the way for its development. Considering this, we believe that sociocultural theory of learning by L. Vygotsky can bring more academic understanding to communicative language teaching. This brings us to the goal of our article, which is to analyze communicative language teaching (CLT) in the framework of sociocultural theory of learning. For deeper understanding we also search through sociocultural theory of cognitive development.As our case is within the Armenian educational environment, we refer to the established New standards of foreign language teaching of the RA (2020). It states that the goal the goal of foreign language teaching is to develop an individual who is capable of communicating and realizing oneself in the modern multilingual and multicultural world. [9, p.4] Considering the Armenian context and the international research we justify the relevance of the article. The novelty of the article revolves around its unique theoretical approach to communicative language teaching. By researching sociocultural theory, we provide deeper cognitive and sociocultural reasons to the theoretical foundation of communicative language teaching especially in the demand of Armenian educational context. For more practical reasoning we will also provide examples of practical implementation of social context in the foreign language classroom.
Keywords: communicative teaching; zone of proximal development; scaffolding; sociocultural theory; method